2014
DOI: 10.4102/ajlm.v3i1.102
|View full text |Cite
|
Sign up to set email alerts
|

Proficiency testing for HIV, tuberculosis and malaria diagnosis in clinical laboratories in Nigeria

Abstract: BackgroundProficiency testing (PT) is a means of verifying the reliability of laboratory results, but such programmes are not readily available to laboratories in developing countries. This project provided PT to laboratories in Nigeria.ObjectivesTo assess the proficiency of laboratories in the diagnosis of HIV, tuberculosis and malaria.MethodsThis was a prospective study carried out between 2009 and 2011. A structured questionnaire was administered to 106 randomly-selected laboratories. Forty-four indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…In this study the average PT performance the 6 PT events for 28 PT programs was 67.75% success rate even though significant improvement is not observed through the trend of PT event which among participated facilities those graded as ACC or UNACC which account 97507 (79.9%) among the total PT challenges distributed and the success rate or the rate of scoring ACC were 66.00%, 67.61%, 67.22%, 67.35%, 67.48% and 70.87% which showed relatively good performance compared to the study conducted among 12 government hospitals laboratories in Addis Ababa, who had been participated in proficiency tasting schemes for 20 clinical laboratories test parameters in 6 cycles from 2012 to 2013 G. C. in over 6 cycle showed that those meet the analytical performance score of 80 and above is 40.42%, 26.67%, 26.67%, 51.67%, 37.09%, 38.37% this indicates no improvement in quality through time [9]. This study was comparable with the study conducted in Nigeria between 2009 and 2011 [7]. Four rounds of pre-characterized plasma panels for HIV, sputum films for tuberculosis and blood films for malaria were distributed quarterly scores increased from 74% to 95% from the first round to the third round, but decreased in the fourth round for HIV PT and average scores increased from 42% in the first round to 78% in the second round; but a decrease to 34% was observed in the fourth round for Tuberculosis PT while Malaria PT performance was 2% at first, but average scores increased between the second and fourth rounds, culminating in a fourth-round score of 39% which showed low performance compared to the study conducted on quality assurance for point of care testing among different heath facilities [11].…”
Section: Performance Ratesupporting
confidence: 73%
“…In this study the average PT performance the 6 PT events for 28 PT programs was 67.75% success rate even though significant improvement is not observed through the trend of PT event which among participated facilities those graded as ACC or UNACC which account 97507 (79.9%) among the total PT challenges distributed and the success rate or the rate of scoring ACC were 66.00%, 67.61%, 67.22%, 67.35%, 67.48% and 70.87% which showed relatively good performance compared to the study conducted among 12 government hospitals laboratories in Addis Ababa, who had been participated in proficiency tasting schemes for 20 clinical laboratories test parameters in 6 cycles from 2012 to 2013 G. C. in over 6 cycle showed that those meet the analytical performance score of 80 and above is 40.42%, 26.67%, 26.67%, 51.67%, 37.09%, 38.37% this indicates no improvement in quality through time [9]. This study was comparable with the study conducted in Nigeria between 2009 and 2011 [7]. Four rounds of pre-characterized plasma panels for HIV, sputum films for tuberculosis and blood films for malaria were distributed quarterly scores increased from 74% to 95% from the first round to the third round, but decreased in the fourth round for HIV PT and average scores increased from 42% in the first round to 78% in the second round; but a decrease to 34% was observed in the fourth round for Tuberculosis PT while Malaria PT performance was 2% at first, but average scores increased between the second and fourth rounds, culminating in a fourth-round score of 39% which showed low performance compared to the study conducted on quality assurance for point of care testing among different heath facilities [11].…”
Section: Performance Ratesupporting
confidence: 73%
“…The proficiency testing performance score for HIV serology was consistently at 100%. Improved PTP in HIV serology score from 74% to 94% in a survey involving 44 laboratories in four trails following staff mentoring have been reported in Nigeria [28]. For the other parameters there was sustained improvement over the study period.…”
Section: Discussionmentioning
confidence: 70%
“…External quality control programmes available Existing external quality programmes for microbiology are scarce, expensive, and address mostly HIV, tuberculosis, and malaria 42,[81][82][83][84][85] Reference laboratories…”
Section: Clinical Decision Makingmentioning
confidence: 99%